Road Safety Challenges in Egypt: A Discussion of Policy Alternatives - ElMoghazi, Yasmine (AUC Knowledge Fountain, 2019)
Road traffic injuries are a growing health epidemic with fatalities and injuries marking damaging emotional, social, and economic impacts on humans, countries and the world. In response, the United Nations proclaimed a decade of action for road safety (2011-2020) to call upon governments across the world to act towards reducing the number of the rising global road traffic fatalities and injuries. The UN introduced a conceptual framework consisting of five pillars (1) road safety management; (2) safer roads and mobility; (3) safer vehicles; (4) safer road users; and (5) post-crash response. Unfortunately, Egypt did not commit to the UN's resolution although the country faces a serious road safety problem. Very little research has been done on road safety in Egypt, and the country lacks a coherent road safety policy with a clear strategy, defined objectives and measurable targets. Moreover, this study found various discrepancies in Egypt's crash data upon examining different reports and publications. To understand the underlying issues of Egypt's poor road safety conditions, a key research question was examined: what are the road safety challenges in Egypt? The results show that Egypt faces deeply rooted problems when it comes to road safety management. For example, the country does not have enough police officers available to enforce the road traffic laws, nor does it have a proper automated system to address the shortage. In addition, the absence of a road safety lead agency with a legal mandate has resulted in the lack of accountability and disorganization of government stakeholders. The failure in the road safety management pillar has caused a domino effect in all the other four pillars. In regard to the safer roads and mobility pillar, the research provides documentations of how the roads are not designed to protect pedestrians and other vulnerable road users. It also shows how newly maintained and paved roads have been damaged only a few months later due to the lack of organization among governmental bodies. This results in high government waste of resources, and the lack of monitoring and evaluation has created an atmosphere for corruption. As for the safer vehicles pillar, vehicles safety standards in Egypt are almost non-existent. Most of the recent cars sold in the market are not equipped with basic safety features such as airbags and/or an Anti-lock Breaking System (ABS). The safer road users pillar also faces a lot of challenges in the presence of the poor law enforcement and the lack of awareness among road users. As for the post-crash response pillar the failures occur due to the limited geographical coverage of ambulances and the challenging access to trauma centers. The challenges in the system result in preventable road traffic deaths and avoidable injuries. Hence, based on the literature and the findings this research draws a set of recommendations focused on establishing a road safety lead agency with a legal mandate to address these challenges.